SHORT TIME RESULT OF PERCUTANEOUS TRANSLUMINAL ANGIOPLASTY ON ISCHEMIA DIABETIC FOOT ULCER - Irawan, Hendry; Mooy, Danny Zefanya; Yasa, Ketut Putu (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â The frequent complication of diabetes mellitus is ischemic diabetic foot ulcers (DFUs). As compared to non-diabetic people, ischemic of foot prevalence is significantly higher in diabetic people. It is related with severe clinical manifestations and the risk of critical limb ischemia and limb loss is increasing. In this case, we performed percutaneous transluminal angioplasty (PTA) in patient with ischemic DFU. A male, 58-year old, complained severe rest pain and gangrene in the fourth toe of the left foot more than 2 months. He had a history of diabetes mellitus type 2 for 4 years ago with uncontrolled blood sugar. We perform PTA to decrease the rest pain and prevent expand of the gangrene. The result of PTA was shown instant effect to reduce rest pain, pulses are easily palpable, and there was no expansion of the gangrene.